Crop production of bacteria - Patten, Ernest Byron (My University, 1898)
Introduction: It is true that oxygen, carbon and hydrogen combine to form cellulose out of which the frame work of vegetation is built, and to form the starches, sugars and gums which make up by far the largest part of the dry weight of vegetable matter; but these appear to be only products which have resulted from the transformations which take place within the protoplasmic substance of which nitrogen sulphur and phosphorus appear to be the controlling life –leading element. The amount of nitrogen required by different plants varies. One kind of grain will require more nitrogen than another. A crop of wheat which yields 30 bushels of grain to the acre requires 48 pounds of nitrogen. One yielding 60 bushels of grain to the acre requires 73.3 pounds of nitrogen. Red clover yielding 2 tons per acre requires 102 pounds of nitrogen. With these figures, it is assumed that no nitrogen is given back to the soil, which, however, is not true regarding clover.
Citation: Patten, Ernest Byron. Crop production of bacteria. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Oxygen; Carbon; Hydrogen; Vegetation; Sugars; Theses; Manuscripts (documents)